IDEOLOGICAL STRENGTHENING, STRATEGIC LEADERSHIP, AND DEPERSONALIZATION: THE TRANSFORMATION OF THE INDONESIAN DEMOCRATIC PARTY OF STRUGGLE 1999-2019 - Kristiyanto, Hasto; Hanief, A (Department of Government, FISIP, Universitas Padjadjaran, 2022)
<span lang=